2018
DOI: 10.1080/00324728.2017.1421254
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant mothers’ preferences for children’s sexes: A register-based study of fertility behaviour in Norway

Abstract: Parental sex preferences have been documented in many native populations, but much less evidence is available on immigrants' preferences for the sexes of their children. Using high-quality longitudinal register data from Norway, a country with a recent immigration history, we estimate hazards regression models of third birth risks by the sex composition of the first two children. A central question in the extant literature is whether the sex preferences of immigrant mothers match those observed in their countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 86 publications
2
15
0
4
Order By: Relevance
“…Second, our findings regarding how duration of residence, age at migration and having a Swedish partner shape childbearing behavior of immigrants improve our understanding of how sub-groups of immigrants adapt to the local conditions of the host country: those who came during childhood or adulthood, those who stay in Sweden for a short or a long period of time. Third, findings of this study provide evidence, from the Swedish context, for the theoretical argument on whether the childbearing behavior of immigrants and their parental sex preferences in the host country are mainly due to the persistence of cultural norms of the home country, and whether the behaviors and preferences that resemble that of the host country are mainly due to the cultural adaptation to the new country (Lillehagen and Lyngstad 2018).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Second, our findings regarding how duration of residence, age at migration and having a Swedish partner shape childbearing behavior of immigrants improve our understanding of how sub-groups of immigrants adapt to the local conditions of the host country: those who came during childhood or adulthood, those who stay in Sweden for a short or a long period of time. Third, findings of this study provide evidence, from the Swedish context, for the theoretical argument on whether the childbearing behavior of immigrants and their parental sex preferences in the host country are mainly due to the persistence of cultural norms of the home country, and whether the behaviors and preferences that resemble that of the host country are mainly due to the cultural adaptation to the new country (Lillehagen and Lyngstad 2018).…”
Section: Introductionmentioning
confidence: 66%
“…Some studies exploring the sex ratio at birth (SRB 1 ) have found elevated ratios in third or higher-order births among immigrant women of an Asian background, indicating sex selection of children among this immigrant group (Almond and Edlund 2008;Almond et al 2013;Dubuc and Coleman 2007;Hwang and Saenz 1997;Mussino et al 2018;Singh et al 2010). A few other studies have looked at parity progression based on the sex composition of previous children (Almond et al 2013;Adsera and Ferrer 2016;Lillehagen and Lyngstad 2018;Okun 1996;Ost and Dziadula 2016;Tang 2013). A common finding of these studies is the extensive sex preference in favor of boys at higher parities among women of East and Southeast Asian origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mussino and Strozza (2012b) arrive at a similar conclusion; the analysis of second-birth rates among immigrants in Italy shows that immigrants from North Africa, particularly those who were in endogamous marriages (co-ethnic partners), had relatively high second-birth rates. Lillehagen and Lyngstad (2018) investigate third-birth rates in Norway and show that immigrant mothers from Pakistan, Turkey, Somalia, and Morocco exhibited a significantly higher likelihood of having a third birth than native Norwegian women. Their analyses also indicate that the sex preferences of immigrants matched those documented for their origin population, especially in case of son preference, supporting theories emphasising cultural persistence in preferences.…”
Section: Recent Research On Childbearing Patterns Among Immigrants Anmentioning
confidence: 99%
“…Preferensi gender ini lebih melekat pada identitas kesukuan dan keluarga dibanding konteks lingkungan sekitar. Kemanapun sebuah keluarga bermigrasi, preferensi gender anak lebih eksis dipilih berdasarkan nilai anak yang berasal dari suku dan keluarga tersebut berasal (11)(23)(24)(25) (26).…”
Section: Preferensi Komposisi Anakunclassified